Bacterial Communities of the Canola Rhizosphere: Network Analysis Reveals a Core Bacterium Shaping Microbial Interactions - Floc’h, Jean-Baptiste; Hamel, Chantal; Lupwayi, Newton; Harker, K. Neil; Hijri, Mohamed; St-Arnaud, Marc (Frontiers in Microbiology, 2020)
The rhizosphere hosts a complex web of prokaryotes interacting with one another that may modulate crucial functions related to plant growth and health. Identifying the key factors structuring the prokaryotic community of the plant rhizosphere is a necessary step towards the enhancement of plant production and crop yield with beneficial associative microorganisms. We used a long-term field experiment conducted at three locations in the Canadian prairies to verify that: (1) the level of cropping system diversity influences the α- and β-diversity of the prokaryotic community of canola (Brassica napus) rhizosphere; (2) the canola rhizosphere community has a stable prokaryotic core; and (3) some highly connected taxa of this community fit the description of hub-taxa. We sampled the rhizosphere of canola grown in monoculture, in a 2-phase rotation (canola-wheat), in a 3-phase rotation (pea-barley-canola), and in a highly diversified 6-phase rotation, five and eight years after cropping system establishment. We detected only one core bacterial Amplicon Sequence Variant (ASV) in the prokaryotic component of the microbiota of canola rhizosphere, a hub taxon identified as cf. Pseudoarthrobacter sp. This ASV was also the only hub taxon found in the networks of interactions present in both years and at all three sites. We highlight a cohort of bacteria and archaea that were always connected with the core taxon in the network analyses.